ANALYSIS OF THE RESULTS OF SURGICAL PROCEDURES ADVISABLE FOR CHRONIC PANCREATITIS WITH THE PREDOMINANT LESION OF THE PANCREATIC HEAD - A. S. Polyakevich; E. M. Blagitko; S. D. Dobrov; G. N. Tolstykh; Yu. V. Chikinev; E. A. Drobyazgin (Сибирский научный медицинский журнал, 2020)
Recently, studies comparing various variants of operations to establish the optimal method of surgical treatment for chronic pancreatitis with pancreatic head lesions from the point of view of evidence-based medicine have been carried out in the world. However, these comparative studies do not take into account differences in the clinical and morphological forms of the disease, in particular, chronic pancreatitis with a predominant and isolated lesion of the head. Subtotal resection of the pancreatic head with proximal pancreatojejunostomy, suitable for an isolated lesion of the head, does not solve all the problems of chronic pancreatitis with a predominant lesion of the head. In this case, the violation of the outflow of pancreatic juice along the pathologically changed main pancreatic duct from the left half of the gland is not eliminated. It is impossible to unambiguously support the hypothesis of the feasibility of performing subtotal resection of the pancreatic head with proximal pancreatojejunostomy in chronic pancreatitis with a predominant lesion of the head with a uniformly expanded main pancreatic duct. With this form of chronic pancreatitis, cicatricial strictures can form in the main pancreatic duct, which can lead to ductal hypertension and serve as an indication for reoperation. The feasibility of using Beger operation in chronic pancreatitis with a predominant lesion of the head is doubtful, since the intersection of the isthmus and the need for a T-shaped longitudinal pancreatojejunostomy makes this intervention technically difficult and unsafe. Based on the studies performed, it is impossible to say with certainty about the reliable advantages of one type of operations over another. To obtain reliable results, it’s necessary to conduct evidence-based studies comparing subtotal resection of the pancreatic head with longitudinal pancreatojejunostomy with other types of interventions only for chronic pancreatitis with a predominant head lesion, excluding from the study patients with chronic pancreatitis with isolated head lesion.